Nutrition and performance in young female cross-country skiers - Kettunen, O. (University of Jyväskylä, 2023)
Cross-country (XC) skiing is an endurance sport in which training significantly increases dietary energy and macronutrient requirements. As inadequate dietary intake may compromise health and performance, this dissertation aimed to investigate if energy availability (EA) and macronutrient intake are associated with performance and physiological symptoms of low EA in young female XC skiers. In addition, the study investigated the extent to which young female XC skiers meet the current nutritional recommendations for endurance athletes. In experiment I, 19 female XC skiers (16-18 years) completed 48-hour food and training logs during normal training period at home and during a 5-day training camp. Anthropometric measurements, fasting blood samples, and performance tests (submaximal running, vertical jumps) were performed on the first and the last morning of the training camp. In experiment II, 27 female XC skiers (15-19 years) completed five 3-day food and training logs during different training periods of the annual training cycle. Laboratory measurements including body composition measurements, fasting blood samples, and performance tests (aerobic capacity, lactate threshold, double poling, vertical jumps) were performed at the end of each training period. Competition performance was determined from the results of Finnish Junior National Championships. The Low Energy Availability in Females Questionnaire (LEAF-Q) and nutrition knowledge questionnaire were completed in both experiments. Most participants had suboptimal EA and carbohydrate intake during all of the training periods despite increasing dietary intake during more intense training periods. Athletes with higher EA and macronutrient intake tended to perform better both in competitions and in laboratory performance tests. In addition, lower EA and carbohydrate intake during the training camp was associated with signs of under-recovery at the end of the camp. Higher nutrition knowledge and lower prevalence of physiological symptoms of low EA (lower LEAF-Q score) were associated with higher carbohydrate intake. In conclusion, young female XC skiers have difficulties to meet optimal EA and carbohydrate intake, which may have a negative impact on their performance and health. These results highlight the importance of enhanced high-quality nutrition education for young female XC skiers.